Rdo rje phag moʼi zab khrid dbaṅ phur thugs thig skor - Bde-baʼi-rdo-rje (s.n., 1970)
Nyingmapa rediscovered liturgical texts connected with the propitiatory worship of Vajravarahi, tantric Buddhist tutelary goddess.